2021
DOI: 10.1071/wf20134
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for effective evaluation and comparison of wildland fire occurrence prediction models

Abstract: Daily, fine-scale spatially explicit wildland fire occurrence prediction (FOP) models can inform fire management decisions. Many different data-driven modelling methods have been used for FOP. Several studies use multiple modelling methods to develop a set of candidate models for the same region, which are then compared against one another to choose a final model. We demonstrate that the methodologies often used for evaluating and comparing FOP models may lead to selecting a model that is ineffective for opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…The classification accuracy may be measured with different metrics of the root mean squared method such as binary classification error rate, negative log-likelihood function, mean absolute error, mean absolute percentage error or area under the ROC curve (AUC). All of them provide similar results, but it is acknowledged that the AUC criterion is not recommended for very imbalanced data sets [57]. XGBoost model exhibits higher accuracy than single decision trees, but the interpretability is also more difficult.…”
Section: Resultsmentioning
confidence: 99%
“…The classification accuracy may be measured with different metrics of the root mean squared method such as binary classification error rate, negative log-likelihood function, mean absolute error, mean absolute percentage error or area under the ROC curve (AUC). All of them provide similar results, but it is acknowledged that the AUC criterion is not recommended for very imbalanced data sets [57]. XGBoost model exhibits higher accuracy than single decision trees, but the interpretability is also more difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that the machine learning models used for FOP in past studies systematically overpredict the probability of wildland fires, and thus are unsuitable for operational use (Phelps and Woolford 2021). We presented methods for fitting properly calibrated FOP models using both statistical and machine learning approaches, and then compared a set of wellcalibrated models for human-caused FOP in Lac La Biche, Alberta.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Phelps and Woolford (2021), we used area under the precision-recall curve (AUC-PR), negative logarithmic score (NLS) and temporal and spatial visualisations to evaluate and compare the models. AUC-PR was computed using the integration approach (Boyd et al 2013;Keilwagen et al 2014) from the PRROC package (Grau et al 2015), while the temporal plots with corresponding root-mean-squared error (RMSE) values were computed using aggregated daily totals across the entire study region.…”
Section: Evaluating and Comparing Model Performancementioning
confidence: 99%
See 2 more Smart Citations